From silver screen to Spanish stage : the humorists of the Madrid vanguardia and Hollywood film - Green, Stuart (Stuart Nishan) (Iberian and Latin American studies., 2011)
This is the first book-length English-language study of a group of five artists closely linked with the Spanish avant-garde in the 1920s and 1930s.